2021
DOI: 10.3390/nano11123369
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Up Colloidal Synthesis of Shape-Controlled Cu-Se-S Nanostructures—Role of Precursor and Surfactant Reactivity and Performance in N2 Electroreduction

Abstract: Copper selenide-sulfide nanostructures were synthesized using metal-organic chemical routes in the presence of Cu- and Se-precursors as well as S-containing compounds. Our goal was first to examine if the initial Cu/Se 1:1 molar proportion in the starting reagents would always lead to equiatomic composition in the final product, depending on other synthesis parameters which affect the reagents reactivity. Such reaction conditions were the types of precursors, surfactants and other reagents, as well as the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Thus, the graphical representation of ( h ν F km ) 2 against h ν can be used to evolve the band gap energy by extrapolating the linear portion to the X -axis ( h ν = 0), as manifested in Figure . It has been found that the band gap of Cu 1.8 Se 0.6 S 0.4 nanopowder is about 1.23 eV (Figure a), which agrees with many previous reports. On the other hand, the band gap energy of Cu 1.8 Se 0.6 S 0.4 is about 3.07 eV (Figure b), which is attributed to the presence of PVDF, which has a large band gap (5.66 eV) leading to widening of the band of the composite. Here, Cu 1.8 Se 0.6 S 0.4 has been mixed and filled inside the PVDF, and now, the band gap is the band gap of the whole composite (mixture) and not for Cu 1.8 Se 0.6 S 0.4 only.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, the graphical representation of ( h ν F km ) 2 against h ν can be used to evolve the band gap energy by extrapolating the linear portion to the X -axis ( h ν = 0), as manifested in Figure . It has been found that the band gap of Cu 1.8 Se 0.6 S 0.4 nanopowder is about 1.23 eV (Figure a), which agrees with many previous reports. On the other hand, the band gap energy of Cu 1.8 Se 0.6 S 0.4 is about 3.07 eV (Figure b), which is attributed to the presence of PVDF, which has a large band gap (5.66 eV) leading to widening of the band of the composite. Here, Cu 1.8 Se 0.6 S 0.4 has been mixed and filled inside the PVDF, and now, the band gap is the band gap of the whole composite (mixture) and not for Cu 1.8 Se 0.6 S 0.4 only.…”
Section: Resultssupporting
confidence: 89%
“…19,20 Several transitional metal chalcogenides have been explored as cathodes, including molybdenum sulfide (MoS 2 ), 21 titanium sulfide (TiS 2 ), 19 vanadium sulfide (VS 2 ), 22 copper selenide (CuSe), 23 copper indium sulfide-selenide (CIS/Se), copper sulfides (Cu 7.2 S 4 ), 24 copper antimony selenide sulfide (CuSbSe x S 2−x ), 25 and copper selenide-sulfide (CuSeS). 26,27 More recently, CuSe witnessed few reports as a promising cathode for rechargeable magnesium-ion batteries (RMB). 23,28 The significant advantage of CuSe is that it depends on the displacement reaction mechanism, which is very favorable in boosting the battery's performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colloidal methods are widely used for the fabrication of advanced nanomaterials and nanocomposites [ 1 , 2 , 3 ]. The use of surfactants for colloidal nanofabrication allows efficient control of particle size and prevention of their agglomeration [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a potential alternative to Haber–Bosch, electrocatalytic nitrogen reduction reaction (NRR) is a green and sustainable method to produce NH 3 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. As we all know, the electrocatalytic NRR process, as opposed to the simple two-electron reaction mechanism of hydrogen evolution reaction (HER), includes numerous multiphase reactions involving six protons, six electrons, and one N 2 and a complicated mass transfer process [ 8 ].…”
Section: Introductionmentioning
confidence: 99%